THINKING AT THE INTERFACE: THEORY AND PRACTICE IN THE SOUTH AFRICAN UNIVERSITY/COMMUNITY RELATIONSHIP - Soudien, Crain (South African Journal of Higher Education, 2016)
The South African university has been the focus of a great deal of global interest in recent years. In bringing together this collection of essays, towards placing this upsurge of interest in clearer perspective, we seek to make the argument that the South African university presents itself as a particularly important case study for understanding how the challenge of thinking - the development of conceptual frameworks, the generation of new theoretical and political positions and, ultimately, the making of new knowledge – in the boundary zone occupied by academics and community members can be undertaken. The essays are critical assessments of work taking place at the University of Cape Town in the interface between the university and the community.